A dialogue of difference: Dionne Brand’s writing within Canadian culture - Danytė, Milda (Literatūra, 2013)
Dionne Brand, a poet, novelist, essayist, life-writer and documentary film-maker, is a relatively well-known figure in the Canadian English-language literary culture. [...]